Rwanda : First Review Under the Policy Coordination Instrument and Monetary Policy Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Rwanda's First Review Under the Policy Coordination Instrument (PCI) and Monetary Policy Consultation. Rwanda's macroeconomic performance under the program remains strong. The PCI-supported program focuses on creating budget space for the implementation of Rwanda's National Strategy for Transformation. The program also calls for improving fiscal transparency, boosting revenue, and supporting the implementation of the new interest rate-based monetary policy framework. Looking ahead, the fiscal deficit path is forecasted to adhere to the fiscal rule under the program, which provides space for the implementation of the National Strategy for Transformation (NST) while safeguarding debt sustainability. The government plans to finance the NST partly through public borrowing, which should continue to be supported by careful debt management. There are several plans underway to increase domestic revenues by boosting the registration of new taxpayers as well as through innovative schemes and greater use of technology to strengthen tax compliance. Further progress on identifying and managing potential government liabilities-so-called fiscal risks-will be important to ensure that public resources are well protected for use on priority spending.